(3EOGQI GdeYQaI (B/s - (3GdcHjSj, UdGM GdOjfs; (3GdeMjGhj, SYO RfGOs ((3GdbGgQI(B: s (3GdefXeI GdYQHjI ddJfejI GdEOGQjI(B, s, 2005)
(3JCWjQ eaGgjej hefWdbGJ fXQjI(B- (3EOGQI GdeYQaI eaGgje CSGSjI(B- (3YedjGJ EOGQI GdeYQaI(B- (3GdYfGUQ GdCSGSjI dEOGQI GdeYQaI hGSJQGJjLjGJgG hebGjjSgG(B- (3JMOjGJ JfajP EOGQI GdeYQaI(B- (3EOGQI GdeYQaI hGdEbJUGO GdeYQaj(B- (3OQGSGJ hfeGPL YGdejI aj eLGd EOGQI GdeYQaI(B.s
Keywords: (3EOGQI GdeYQaIs; (3GdeYQaIs